Silicon-based negative electrode active material, preparation method thereof and all-solid-state lithium ion battery
By uniformly covering the phosphorus and sulfur layer on the surface of silicon carbon materials, the interface contact between the sulfide electrolyte and the silicon carbon negative electrode is improved, and the problem of poor interface contact in sulfide all-solid lithium-ion batteries is solved, and the battery's rate performance and cycle life are improved. .
Patent Information
- Application Number
- CN202411424651.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-02-18
AI Technical Summary
In sulfide all-solid lithium-ion batteries, the interface contact between the silicon carbon negative electrode and the sulfide electrolyte is poor, resulting in a large interface resistance and affecting the electrochemical performance.
The silicon-based negative electrode active material combined with a silicon-carbon material and a phosphorus-sulfur coating layer is used to improve the interface contact between the sulfide electrolyte and the negative electrode by uniformly covering the phosphorus-sulfur layer on the surface of the silicon-carbon material.
It improves lithium ion transmission dynamics, enhances rate performance and cycle life, and achieves high energy density and excellent electrochemical performance of silicon-based anode-sulfide all-solid-state batteries.
Smart Images

Figure CN119480951A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-based negative electrode active material and a preparation method thereof, and an all-solid-state lithium-ion battery. Background Art
[0002] In order to meet the growing demand for smart electronic devices and electric vehicles, it is of great significance to develop lithium-ion batteries with high energy density and high power density, among which the safety of lithium-ion batteries has become a key indicator. As a potential excellent candidate for achieving high energy density and high power density, all-solid-state batteries have safety advantages that liquid lithium-ion batteries cannot match. All-solid-state batteries using sulfide electrolytes have attracted much attention due to their high ionic conductivity and higher wettability compared to oxide systems, which allows better contact with active materials and lower interfacial resistance.
[0003] In order to apply sulfide solid electrolytes, various negative electrode materials have been studied, such as silicon, graphite, lithium metal, etc. The silicon negative electrode has a low potential (0.4V vs Li / Li + ) and high theoretical specific capacity (3579mAh / g), but it will undergo huge volume expansion and contraction during the charge and discharge process, which can easily cause damage to the electrode structure; the metallic lithium negative electrode also has the advantages of low potential and high theoretical specific capacity (3860mAh / g), but it will form lithium dendrites during the charge and discharge process; for the graphite negative electrode, its theoretical specific capacity is lower (372mAh / g).
[0004] Silicon-based negative electrodes have developed a variety of paths to improve the huge volume expansion and contraction of materials during charging and discharging, including nano-silicon, porous silicon, silicon-carbon materials, etc. Among them, silicon-carbon materials have mainly moved towards the route of chemical vapor deposition of nano-silicon on porous carbon over the years. At present, the most excellent chemical vapor deposition silicon-carbon can achieve a volume expansion and contraction of <100%, which can meet the needs of liquid lithium-ion batteries. However, the use of chemical vapor deposition silicon-carbon in sulfide all-solid-state batteries does not show the same excellent electrochemical performance as in liquid electrolyte systems. The main reasons include: (1) The poor contact between the silicon-carbon negative electrode and the sulfide electrolyte causes a large interface resistance; (2) The reduction and decomposition of the sulfide electrolyte on the surface of the carbon material. Most sulfide electrolytes will undergo thermodynamic decomposition at low potentials and degrade into byproducts with low ionic conductivity, thereby destroying the interface. Therefore, it is crucial to improve the interface stability between the silicon-carbon negative electrode and the sulfide solid electrolyte.
[0005] Therefore, it is necessary to provide a silicon-based negative electrode active material and a preparation method thereof and an all-solid-state lithium-ion battery to improve the interface contact between the sulfide electrolyte and the negative electrode, while improving the rate performance and cycle life of the battery. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a silicon-based negative electrode active material and a preparation method thereof and an all-solid-state lithium-ion battery to improve the interface contact between the sulfide electrolyte and the negative electrode, while improving the battery's rate performance and cycle life.
[0007] A first aspect of the present invention provides a silicon-based negative electrode active material.
[0008] Specifically, it includes silicon-carbon material and phosphorus-sulfur coating;
[0009] The phosphorus-sulfur coating layer coats the silicon-carbon material;
[0010] The content of phosphorus in the silicon-based negative electrode active material is 1-10%, and the content of sulfur is 0.1-3%.
[0011] Preferably, the content of phosphorus is 1-8%, and the content of sulfur is 0.1-0.6%.
[0012] Preferably, the particle size of the silicon-carbon material is 1 to 50 μm.
[0013] More preferably, the particle size of the silicon-carbon material is 1 to 20 μm.
[0014] More preferably, the particle size of the silicon-carbon material is 10 to 15 μm.
[0015] Preferably, the thickness of the phosphorus-sulfur coating layer is 1 to 200 nm.
[0016] More preferably, the phosphorus-sulfur coating layer has a thickness of 1 to 30 nm.
[0017] More preferably, the thickness of the phosphorus-sulfur coating layer is 5 to 30 nm.
[0018] A second aspect of the present invention provides a method for preparing a silicon-based negative electrode active material.
[0019] Specifically, the following steps are included:
[0020] The silicon-carbon material is mixed with sulfur and phosphorus, and then heated for the first time and kept warm for the first time under a protective gas atmosphere, and then heated for the second time and kept warm for the second time, cooled and kept warm for the third time to obtain the silicon-based negative electrode active material.
[0021] The first heat preservation after the first heating can promote the decomposition of sulfur and its entry into the carbon pores of the silicon-carbon material, while the second heating and the second heat preservation can promote the sublimation of phosphorus, and further control the uniform deposition of phosphorus on the surface of the silicon-carbon material by cooling.
[0022] Preferably, the mass ratio of the phosphorus element to the silicon-carbon material is 1-30:100.
[0023] Further preferably, the mass ratio of the phosphorus element to the silicon-carbon material is 1-20:100.
[0024] More preferably, the mass ratio of the phosphorus element to the silicon-carbon material is 1-12:100.
[0025] Preferably, the mass ratio of the sulfur element to the phosphorus element is 1-10:(10-100).
[0026] More preferably, the mass ratio of the sulfur element to the phosphorus element is 1 to 6:100.
[0027] More preferably, the mass ratio of the sulfur element to the phosphorus element is 2 to 6:100.
[0028] Preferably, the temperature of the first heating is 100-200°C.
[0029] More preferably, the first heating temperature is 150-200°C.
[0030] More preferably, the temperature of the first heating is 155°C.
[0031] Preferably, the first insulation time is 1 to 24 hours.
[0032] More preferably, the first insulation time is 12 to 24 hours.
[0033] More preferably, the first insulation time is 12 hours.
[0034] Preferably, the temperature of the second heating is 400-700°C.
[0035] More preferably, the second heating temperature is 450-500°C.
[0036] More preferably, the temperature of the second heating is 460°C.
[0037] Preferably, the second insulation time is 1 to 24 hours.
[0038] More preferably, the second insulation time is 1 to 5 hours.
[0039] More preferably, the second insulation time is 2 hours.
[0040] Preferably, the cooling temperature is 100-300°C.
[0041] More preferably, the cooling temperature is 250-300°C.
[0042] More preferably, the cooling temperature is 280°C.
[0043] Preferably, the third insulation time is 1 to 24 hours.
[0044] More preferably, the third insulation time is 1 to 12 hours.
[0045] More preferably, the third insulation time is 12 hours.
[0046] Preferably, the phosphorus element includes at least one of red phosphorus, white phosphorus and black phosphorus.
[0047] Preferably, the sulfur element includes at least one of sulfur, cycloheptasulfur, cyclodecasulfur, cyclododecsulfur, cyclooctadecsulfur, cycloeicossulfur, and chain sulfur.
[0048] Preferably, the mixing treatment method includes at least one of high-speed mechanical mixing, ball milling mixing, grinding mixing, and liquid phase mixing.
[0049] Preferably, the reactor is a high-pressure reactor.
[0050] Preferably, the protective gas includes at least one of argon, helium, nitrogen and carbon dioxide. The air in the reactor is replaced to prevent the influence of air on the material.
[0051] A third aspect of the present invention provides a negative electrode.
[0052] Specifically, the negative electrode includes the silicon-based negative electrode active material provided in the first aspect.
[0053] A fourth aspect of the present invention provides an all-solid-state lithium-ion battery.
[0054] Specifically, the all-solid-state lithium-ion battery includes the negative electrode provided by the third aspect.
[0055] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0056] The silicon-based negative electrode active material prepared by the present invention realizes good interface contact between the sulfide electrolyte on the negative electrode side of the sulfide all-solid-state battery and the silicon-based negative electrode by using sulfur to uniformly coat phosphorus on the surface of the silicon-carbon material, improves the lithium ion transmission kinetics on the negative electrode side, and improves the rate performance of the silicon-based negative electrode active material; at the same time, the cycle stability of the silicon-carbon material is effectively utilized, thereby greatly improving the performance of the silicon-carbon material in the sulfide all-solid-state battery. The present invention realizes the synergy of high energy density, high cycle life, and excellent rate performance of the silicon-based negative electrode-sulfide all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 This is a SEM image of the silicon-based negative electrode active material prepared in Example 3 of the present invention;
[0058] Figure 2 The SEM and EDS images of the silicon-based negative electrode active material prepared in Example 3 of the present invention;
[0059] Figure 3 The first cycle charge and discharge curve diagram of the all-solid-state lithium-ion battery formed in Example 3 of the present invention;
[0060] Figure 4 This is a rate performance diagram of the all-solid-state lithium-ion battery composed of Example 3 of the present invention and Comparative Example 2. DETAILED DESCRIPTION
[0061] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0062] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0063] Example 1
[0064] A silicon-based negative electrode active material and a preparation method thereof.
[0065] The silicon-based negative electrode active material includes a silicon-carbon material and a phosphorus-sulfur coating layer coating the silicon-carbon material: the particle size of the silicon-carbon material is 10.23 μm, and the thickness of the phosphorus-sulfur coating layer is 29 nm; the silicon-based negative electrode active material contains 57.03% silicon, 36.41% carbon, 6.15% phosphorus and 0.41% sulfur.
[0066] The specific preparation method is as follows:
[0067] 45.0g of silicon-carbon material, 0.25g of sulfur and 4.75g of red phosphorus were placed in a wall breaking machine for high-speed mechanical mixing for 5 minutes to obtain a mixed sample, and the mixed sample was placed in a high-pressure reactor, argon gas was introduced to replace the air, and the stirring speed was set to 300rpm; the temperature was controlled to rise to 155°C for the first heating, and then kept warm for 12h for the first time, then raised to 460°C for the second heating and kept warm for 2h for the second time, cooled to 280°C and kept warm for a third time for 12h, and finally after the reactor was cooled to room temperature, a silicon-based negative electrode active material was obtained.
[0068] Example 2
[0069] A silicon-based negative electrode active material and a preparation method thereof.
[0070] The silicon-based negative electrode active material includes a silicon-carbon material and a phosphorus-sulfur coating layer coating the silicon-carbon material: the particle size of the silicon-carbon material is 10.23 μm, and the thickness of the phosphorus-sulfur coating layer is 23 nm; the silicon-based negative electrode active material contains 58.93% silicon, 35.77% carbon, 5.07% phosphorus and 0.23% sulfur.
[0071] The specific preparation method is as follows:
[0072] Compared with Example 1, the difference is that the masses of silicon-carbon material, sulfur, and red phosphorus are adjusted to 45.0 g, 0.125 g, and 4.875 g, respectively, and the remaining steps are the same as Example 1.
[0073] Example 3
[0074] A silicon-based negative electrode active material and a preparation method thereof.
[0075] The silicon-based negative electrode active material includes a silicon-carbon material and a phosphorus-sulfur coating layer coating the silicon-carbon material: the particle size of the silicon-carbon material is 11.23 μm, and the thickness of the phosphorus-sulfur coating layer is 6 nm; the silicon-based negative electrode active material contains 58.68% silicon, 39.28% carbon, 1.48% phosphorus and 0.56% sulfur.
[0076] The specific preparation method is as follows:
[0077] Compared with Example 1, the difference is that the masses of silicon-carbon material, sulfur, and red phosphorus are adjusted to 48.5 g, 0.075 g, and 1.425 g, respectively, and the remaining steps are the same as Example 1.
[0078] Example 4
[0079] A silicon-based negative electrode active material and a preparation method thereof.
[0080] The silicon-based negative electrode active material includes a silicon-carbon material and a phosphorus-sulfur coating layer coating the silicon-carbon material: the particle size of the silicon-carbon material is 11.23 μm, and the thickness of the phosphorus-sulfur coating layer is 5 nm; the silicon-based negative electrode active material contains 58.41% silicon, 40.01% carbon, 1.36% phosphorus and 0.22% sulfur.
[0081] The specific preparation method is as follows:
[0082] Compared with Example 1, the difference is that the masses of silicon-carbon material, sulfur, and red phosphorus are adjusted to 48.5 g, 0.0375 g, and 1.4625 g, respectively, and the remaining steps are the same as Example 1.
[0083] Comparative Example 1
[0084] A silicon-based negative electrode active material and a preparation method thereof.
[0085] Silicon-based negative electrode active material: The particle size of the silicon-carbon material is 11.23μm, and the thickness of the phosphorus-sulfur coating layer is 189nm; the silicon content of the silicon-based negative electrode active material is 55.62%, the carbon content is 34.48%, the phosphorus content is 9.42%, and the sulfur content is 0.48%.
[0086] The specific preparation method is as follows: silicon-carbon material, sulfur and red phosphorus are ball-milled at 600 rpm for 3 h to obtain silicon-based negative electrode active material. The amount of each material is the same as that in Example 1.
[0087] Comparative Example 2
[0088] A silicon-based negative electrode active material and a preparation method thereof.
[0089] The silicon-carbon material in Example 1 is directly used as a silicon-based negative electrode active material, wherein the silicon content of the silicon-based negative electrode active material is 59.46%, the carbon content is 40.54%, the phosphorus content is 0%, and the sulfur content is 0%.
[0090] Performance testing:
[0091] 1. Scanning electron microscope and energy dispersive X-ray spectroscopy.
[0092] The silicon-based negative electrode active material of Example 3 was tested by scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS). The results are as follows: Figure 1 , 2 As shown. The silicon-carbon material presents a micron-level particle size distribution. Through SEM, it can be seen that a layer of material is coated on the surface of the material. Through EDS analysis, it can be concluded that the coating layer is evenly distributed with P and S elements, indicating that the present invention can evenly coat P and S on the surface of the silicon-carbon material. The evenly coated P material will serve as a bridge between the silicon-carbon material and the sulfide solid electrolyte to prevent the decomposition and degradation of the sulfide solid electrolyte in the silicon-carbon material. At the same time, during the first lithium insertion process, P will react with Li + Combined with Li3P to form high ionic conductivity, it can effectively improve the cycle stability and rate performance of the material as the main component of the SEI film on the surface of the silicon-carbon negative electrode.
[0093] 2. Characterization of physical and chemical properties of materials.
[0094] ICP tests were performed on Examples 1 to 4 and Comparative Examples 1 to 2 to obtain the contents of P and S elements in each silicon-based negative electrode active material, and the carbon content of the silicon-carbon material was tested by a carbon-sulfur analyzer to infer the content of silicon element. The results are shown in the above examples.
[0095] The P content of the silicon-based negative electrode active material in Examples 1-2 is 6.15% and 5.07%, which is lower than the total amount of added P of 9.9%. The main reason is that part of the P is not coated on the surface of the material, but deposited on the wall of the reactor. The P content of the silicon-based negative electrode active material in Examples 3-4 is lower than 3% due to this. A higher P content will consume more lithium source during the first lithium insertion process, resulting in a decrease in the first coulombic efficiency of the material. Therefore, by adjusting the content of P and S, the thickness of the surface coating layer can be adjusted, effectively improving the first coulombic efficiency of the material.
[0096] 3. Electrochemical performance test.
[0097] The silicon-based negative electrode active materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were mixed with LiP6S5Cl, VGCF, and PTFE in a mass ratio of 60:40:2:1 to form a negative electrode, and a negative electrode sheet of a suitable size was obtained through a roller pressing and slicing process. Each negative electrode sheet was placed in a polyetheretherketone tube with a diameter of 10 mm, and then 100 mg of LiP6S5Cl was weighed and added to the tube, and pressed and molded at a pressure of 30 MPa and tightly contacted with the negative electrode sheet. Finally, an indium sheet and a lithium sheet were added to the other side of the solid electrolyte, and pressed and molded at a pressure of 4 t to prepare all-solid-state lithium-ion batteries with a three-layer structure (negative electrode / solid electrolyte / Li-In alloy).
[0098] (1) First Coulomb efficiency test:
[0099] The first coulombic efficiency (first efficiency) test was carried out on the all-solid-state lithium-ion batteries composed of Examples 1 to 4 and Comparative Examples 1 to 2. Each all-solid-state lithium-ion battery was charged and discharged at a rate of 0.1C. The first coulombic efficiency = first discharge capacity / first charge capacity × 100%. The results are shown in Table 1.
[0100] Table 1 First performance test results of all-solid-state lithium-ion batteries composed of Examples 1 to 4 and Comparative Examples 1 to 2
[0101] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 First effect% 91.34 91.59 92.07 91.23 82.14 86.72
[0102] As can be seen from Table 1, the all-solid-state lithium-ion batteries composed of Examples 1 to 4 exhibit a relatively high first efficiency, wherein the efficiency of Example 3 is 92.07% (e.g. Figure 3This is attributed to the formation of an artificial SEI film on the surface of the silicon-carbon negative electrode. The P uniformly coated on the surface effectively blocks the contact between the sulfide electrolyte and the silicon-carbon material, while avoiding the degradation and decomposition of the sulfide electrolyte on the negative electrode surface, which has a high Li + As the main component of SEI film, Li3P with high conductivity effectively ensures the + transmission.
[0103] (2) Rate performance test:
[0104] The rate performance test of the all-solid-state lithium-ion batteries composed of Example 3 and Comparative Example 2 was carried out, and the test conditions were as follows: The test conditions were rate performance at different current densities: each all-solid-state lithium-ion battery was charged and discharged at 60°C with currents of 0.1C, 0.3C, 0.5C, 0.8C, 1C and 2C and a cut-off voltage of -0.61 to 1.5V. The battery was tested under a pressure of 25MPa, and the results were as follows: Figure 4 As shown. Figure 4 It can be seen that Example 3 exhibits excellent rate performance, which is attributed to the fact that the P coated on its surface effectively inhibits the degradation and decomposition of the sulfide solid electrolyte in the silicon-based negative electrode active material, and the Li3P after lithium insertion has high ionic conductivity, which effectively stabilizes the Li + transmission, which is beneficial to Li + Fast transmission.
[0105] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.
Claims
1. A silicon-based negative electrode active material, characterized in that: including silicon-carbon material and phosphorus-sulfur coating; The phosphorus-sulfur coating layer coats the silicon-carbon material; The content of phosphorus in the silicon-based negative electrode active material is 1-10%, and the content of sulfur is 0.1-3%.
2. The silicon-based negative electrode active material according to claim 1, characterized in that: The particle size of the silicon-carbon material is 1 to 50 μm.
3. The silicon-based negative electrode active material according to claim 1, characterized in that: The thickness of the phosphorus-sulfur coating layer is 1 to 200 nm.
4. The method for preparing a silicon-based negative electrode active material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The silicon-carbon material is mixed with sulfur and phosphorus, and then heated for the first time and kept warm for the first time under a protective gas atmosphere, and then heated for the second time and kept warm for the second time, cooled and kept warm for the third time to obtain the silicon-based negative electrode active material.
5. The preparation method according to claim 4, characterized in that: The mass ratio of the phosphorus element to the silicon-carbon material is 1 to 30:
100.
6. The preparation method according to claim 4, characterized in that: The mass ratio of the sulfur element to the phosphorus element is 1-10:(10-100).
7. The preparation method according to claim 4, characterized in that: The temperature of the first heating is 100-200°C.
8. The preparation method according to claim 4, characterized in that: The temperature of the second heating is 400-700°C.
9. A negative electrode, characterized in that The negative electrode comprises the silicon-based negative electrode active material according to any one of claims 1 to 3.
10. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the negative electrode according to claim 9.
Citation Information
Cited By
Phosphorus oxide coated silicon-containing material, preparation method thereof and application of phosphorus oxide coated silicon-containing material in sulfide solid-state battery negative electrode material
CN122348196A